CRISPR/Cas9-Based Genome Editing for Disease Modeling and Therapy: Challenges and Opportunities for Nonviral Delivery - Wang, Hong-Xia; Li, Mingqiang; Lee, Ciaran M; Chakraborty, Syandan; Kim, Hae-Won; Bao, Gang; Leong, Kam W (Chemical reviews, 2017)
Genome editing offers promising solutions to genetic disorders by editing DNA sequences or modulating gene expression. The clustered regularly interspaced short palindromic repeats (CRISPR)/associated protein 9 (CRISPR/Cas9) technology can be used to edit single or multiple genes in a wide variety of cell types and organisms in vitro and in vivo. Herein, we review the rapidly developing CRISPR/Cas9-based technologies for disease modeling and gene correction and recent progress toward Cas9/guide RNA (gRNA) delivery based on viral and nonviral vectors. We discuss the relative merits of delivering the genome editing elements in the form of DNA, mRNA, or protein, and the opportunities of combining viral delivery of a transgene encoding Cas9 with nonviral delivery of gRNA. We highlight the lessons learned from nonviral gene delivery in the past three decades and consider their applicability for CRISPR/Cas9 delivery. We also include a discussion of bioinformatics tools for gRNA design and chemical modifications of gRNA. Finally, we consider the extracellular and intracellular barriers to nonviral CRISPR/Cas9 delivery and propose strategies that may overcome these barriers to realize the clinical potential of CRISPR/Cas9-based genome editing.